Equation of State for the Lennard-Jones Fluid - Thol, Monika; Rutkai, Gabor; Köster, Andreas; Lustig, Rolf; Span, Roland; Vrabec, Jadran (Journal of physical and chemical reference data, 2016)
An empirical equation of state correlation is proposed for the Lennard-Jones model fluid. The equation in terms of the Helmholtz energy is based on a large molecular simulation data set and thermal virial coefficients. The underlying data set consists of directly simulated residual Helmholtz energy derivatives with respect to temperature and density in the canonical ensemble. Using these data introduces a new methodology for developing equations of state from molecular simulation. The correlation is valid for temperatures 0.5 < T/T c < 7 and pressures up to p/p c = 500. Extensive comparisons to simulation data from the literature are made. The accuracy and extrapolation behavior are better than for existing equations of state.